Commemorating End Poverty Day - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank, discusses the goals of the World Bank Group, aligned to support the poor and the vulnerable, and to preserve our planet for future generations. He talks about the report "Poverty in a Rising Africa" that traces two decades of unprecedented economic growth on the continent with messages that are both encouraging and sobering. He speaks about how economic growth coupled with specific health and education interventions have contributed to improving people’s lives, and contributed in many countries, such as Ghana, to major reductions in poverty. He talks about the structural transformation, a shift out of agriculture that led to an increase in non-agricultural self-employment and, to a lesser degree, wage jobs in Ghana. He speaks about how improving the agricultural sector will be critical to further reduce extreme poverty in the country. He commends Ghana that has invested in its people, specifically in education in most parts of the country. He appreciated the country’s urban areas that have grown quickly, creating more and higher-paying jobs.